Assuan, Ägypten: Die frühislamische Nekropole von Assuan - Speiser, Philipp (e-Forschungsberichte des DAI, 2023)
The so-called Fatimid Cemetery covers an area of c. 600 × 500 m and contains over 50 mausoleums and hundreds of ancient and modern tombs. It is located south of the historic town of Aswan. The aim of the project is a documentation of multiple aspects of the cemetery and its protection. In 2012 and 2013, research on the site concentrated on geomorphology and the quarries. Several tombs and mausoleums have been restored, while a visitors’ circuit including information panels is currently being installed.